Physiological responses of Phaseolus lunatus L. submitted to irrigation with saline water and potassium fertilization (Research, Society and Development, 2022)
The objective of this work was to evaluate the development of fava beans (Phaseolus lunatus L.) under different levels of irrigation water salinity and different doses of potassium fertilization. The experiment was carried out at the Federal University of  Paraíba, Areia, Paraíba, Brazil. Three electrical conductivities of irrigation water (0, 0.3 and 6.0 dS m-1) and three doses of phosphate fertilization (0, 30 and 60 kg of K2O) were used. The following were analyzed: plant height and number of leaves, fresh mass of the aerial part of the plant, fresh mass of the root, dry mass of the plant and dry mass of the roots. According to the results, it was observed that potassium fertilization induced an increase in the number of leaves, in the treatment with 60 kg ha-1. The increase in sodicity led to a decrease in production at the level of 6 dS m-1. The best bean production was obtained with the dosage of 30 kg ha-1 K2O. Since the increase in the salinity of the irrigation water inhibits the phenological development of the fava bean, as it makes it difficult for the plants to absorb potassium, since this nutrient is essential for the production of phytomass. Thus, it is possible to conclude that saline irrigation water with electrical conductivity of 0.3 and 6.0 dS m-1 inhibits the phenological development of the fava bean. The dose of 30 t ha-1 of potassium favored the increase in the mass of fresh and dry bean matter.